2020
DOI: 10.1111/jpn.13422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with herbal extract mixture on growth performance, organ weight and intestinal morphology in weaning piglets

Abstract: Background Many countries are increasingly prohibiting the addition of antibiotics in livestock diets. Therefore, herb extracts have gradually drawn attention to substitute antibiotics. Our present study aimed to determine the effects of herbal extract mixture (HEM) in dietary on growth performance, organ weight, intestinal morphology and intestinal nutrient transporters in weaned pigs. Methods 27 piglets (Duroc × [Landrace × Yorkshire]; Body Weight (BW) = 5.99 ± 0.13 kg) were weaned at day 21 and randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry (4,17), especially in weaning pigs (7,8). The inconsistent results often occurred concerning the effects of MOA, although MOA always performed a positive impact (18,19). In our paper, we focused on the serum immune function, antioxidant capacity, pH value, tight junction, and microbiota of intestine in 21 and 42 d broilers in terms of their being affected by dietary supplemented with MOA at different levels, which would be helpful in determining the appropriate level of MOA and in confirming whether MOA plays a role on intestine regarding antioxidant systems, digestive enzyme activity, mechanical barrier, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry (4,17), especially in weaning pigs (7,8). The inconsistent results often occurred concerning the effects of MOA, although MOA always performed a positive impact (18,19). In our paper, we focused on the serum immune function, antioxidant capacity, pH value, tight junction, and microbiota of intestine in 21 and 42 d broilers in terms of their being affected by dietary supplemented with MOA at different levels, which would be helpful in determining the appropriate level of MOA and in confirming whether MOA plays a role on intestine regarding antioxidant systems, digestive enzyme activity, mechanical barrier, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these plant extracts ( Lonicera japonica, Astragalus membranaceus , Eucommia folium , and Codonopsis pilosula ) has not been fully investigated in weaning piglets. Moreover, our previous study has shown that dietary supplementation of the herbal extract mixture (HEM), which contains golden-and-silver honeysuckle ( Lonicera japonica ), huangqi ( Astragalus membranaceus ), duzhong leaves ( Eucommia folium ), and dangshen ( Codonopsis pilosula ), improves intestinal morphology through increasing the ratio of villus height to crypt depth in the duodenum, and elevates the mRNA expression of nutrient transporters in the ileum of weaning piglets ( Wang et al, 2020 ). Thus, in the present study, we aimed to further investigate the effects of HEM on the antioxidant capacity and colonic microbiota of weaning piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, L. japonica extract can improve rumen microbial diversity and improve rumen fermentation capacity ( Tang et al, 2018a ). In pig production, herbal extract mixture (HEM) may have a better application effect ( Liu W. et al, 2016 ; Wang M. et al, 2020 ). For instance, Liu W. et al (2016) indicated that dietary supplementation with a mixture of 55% Scutellaria baicalensis extract and 25% L. japonica extract administration could improve growth performance and nutrient digestibility, decrease serum cortisol levels, as well as benefit the meat quality in finishing pigs, and Wang Y. et al (2020) showed that dietary supplementation with 1,000 mg/kg a mixture extract of golden-and-silver honeysuckle ( L. japonica Thunb.…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%